Obstacles for Applying The STEM Approach in Teaching Mathematics from The Point of View of Public School Teachers in Ajloun Governorate - Enizat, Hasan Ibrahim Mahmoud (Journal of Educational and Psychological Sciences, 2022)
This Study aimed to identify the obstacles for applying the STEM approach in teaching Mathematics from the point of view of public school teachers in Ajloun Governorate, the researcher used the Descriptive approaches, study Sample consisted from (130) Female and male mathematics teacher, chosen randomly, to collect data Questioner used, which consisted (26) paragraph divided to three sector, the result of SPSS analysis shown that the degree of the obstacles for applying the STEM approach in teaching Mathematics from the point of view of public school teachers in Ajloun Governorate was High with average (3.77 out of 5) , the obstacles related to the students got the highest average (3.80) with a grade of (high), then the obstacles related to the educational environment with an average of (3.77) and finally the obstacles related to the educational content with an average of (3.73) and both rated (High) The finding also showed there is no statistically significant differences at (α≤0.05) refers to teacher sex (male and female) in addition there were statistically significant differences refers to teacher qualification in favor of (High educating). The study recommended the necessity of achieving the needs of mathematics teaching in public schools in Ajloun governorate according to the STEM approach, and that the Curriculum Department should update the mathematics curricula and adapt the curriculum in line with the nature of the STEM approach.
Keywords: STEM Approach; Mathematics; Teacher Perspective; Ajloun Governorate